Flexural and Shear Behaviour of Reinforced Concrete Slab With PVC Pipe as A Cavity Forming in Two-Way System - Wahyu Mahendra Tria Atmadja; Herman Parung; Rita Irmawaty; Arwin Amiruddin (IPTEK The Journal for Technology and Science, 2020)
Piping modifications Polyvinyl Chloride as forming a hollow cavity in the concrete slab is one alternative to reduce the self-weight of structure. The placement of PVC pipe that has been modified on the concrete tensile area is expected not to reduce the bending strength of the plate. In the study, the analysis was compared to reinforced concrete slab massive (PB-1) with a hollow reinforced concrete slab PVC (PB-2) with the same thickness and compared well with hollow reinforced concrete slab PVC (PB-3) with an equal volume of the concrete slab massive reinforced (PB-1). All test objects have the same dimensions, including the number and spacing of reinforcement. The analysis method of the moment coefficient obtained flexural strength of PB-1 amounted to 328.175 kN, plate PB-2 amounted to 329.624 kN, and the plate of PB-3 amounted to 387.184 kN. While the results of the analysis using the Navier method deflections values obtained for the plate PB-1, PB-2, and PB-3 are 0.0948 mm, 0.33952 mm, and 0.04267 mm, respectively. Shear forces values for plate PB-1, PB-2 and PB-3 is 965.908 kN, 231.818 kN and 281.429 kN respectively.